Accountability: Efforts to Prevent Rush Money at Village Credit Institutions in Buleleng Regency - Budiasni, Ni Wayan Novi; Ayuni, Ni Made Sri (International Journal of Social Science and Business, 2021)
Ensuring the confidence of customers and other stakeholders, LPD requires an internal control system, presentation of financial statements and accountability. The purpose of this research is to know the implications of the internal control system and the presentation of financial statements to accountability. This study used quantitative method, population of 149 LPD that is still operating and selected 60 lpd samples in Buleleng Regency.Â  Questionnaire as an instrument to collect research data. The analysis technique used is SEM (Structural Equation Modeling) with PLS (Partial Least Square) method. Based on the first hypothesis it appears that the relationship between internal control system variables and accountability of parameter coefficients 0.364 with a statistical t value of 4.056 greater than the table t value of 1,960 (4,056>1,960). Similarly, the second hypothetical relationship between the presentation of financial statements has a parameter coefficient value of 0.525 with a statistical t value of 6.362 greater than the table t of 1,960 (6,362>1,960). Based on the results of the study, it can be concluded that the internal control system is positively related to accountability, and the presentation of financial statements relates positively to accountability.